2019
DOI: 10.1111/aej.12373
|View full text |Cite
|
Sign up to set email alerts
|

Root canal filling quality of mandibular molars with EndoSequence BC and AH Plus sealers: A micro‐CT study

Abstract: The aim of this study was to compare, by micro-computed tomography (micro-CT) analysis, the obturation quality of two filling methods: the single-cone technique with the bioceramic EndoSequence BC sealer and the continuous wave technique with the resin-based AH Plus sealer. Twenty mandibular molars were divided into two groups (n = 10) according to the sealer used. Only the mesial roots, which are known to have mostly two canals, were used. The specimens were scanned before and after instrumentation and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
(59 reference statements)
2
15
0
1
Order By: Relevance
“…Evaluation of obturation quality in the mesial roots of mandibular molars and the use of GuttaFlow Bioseal was corroborated with the past studies [26,27]. OrthoMTA (BioMTA, Seoul, South Korea) [26] and Endosequence BC (Brasseler USA, Savannah, GA, USA) [27] have both been investigated in the past, but the present study focuses on GuttaFlow Bioseal (Coltène/Whaledent) considering its excellent properties to seal the root canal system.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Evaluation of obturation quality in the mesial roots of mandibular molars and the use of GuttaFlow Bioseal was corroborated with the past studies [26,27]. OrthoMTA (BioMTA, Seoul, South Korea) [26] and Endosequence BC (Brasseler USA, Savannah, GA, USA) [27] have both been investigated in the past, but the present study focuses on GuttaFlow Bioseal (Coltène/Whaledent) considering its excellent properties to seal the root canal system.…”
Section: Resultssupporting
confidence: 59%
“…Evaluation of obturation quality in the mesial roots of mandibular molars and the use of GuttaFlow Bioseal was corroborated with the past studies [26,27]. OrthoMTA (BioMTA, Seoul, South Korea) [26] and Endosequence BC (Brasseler USA, Savannah, GA, USA) [27] have both been investigated in the past, but the present study focuses on GuttaFlow Bioseal (Coltène/Whaledent) considering its excellent properties to seal the root canal system. SEM imaging was selected in the present study because of its ability to produce high resolution images at higher magnifications compared to the conventional microscopy and this was congruent with previous studies [4,[39][40][41][42][43][44][45][46][47].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The sealers used in the present study have similar physicochemical characteristics, such as high flow, biocompatibility and radiopacity 7,21 , although their compositions differ and also their adhesion mechanism to dentin. AH Plus is an epoxy resin sealer that interacts chemically with the root dentin collagen with covalent bonds between its epoxy rings and collagen amine groups 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Micro-CT is a method that has been widely used in recent years to evaluate RCS anatomy, obturation and retreatment through three-dimensional analysis 10,11,15,20,21 . In the present study, micro-CT showed 23% remaining filling material in the AHP group, whereas that in the TF group was 28%; the two groups were not statistically significantly different.…”
Section: Discussionmentioning
confidence: 99%